More Than Three Years for Normalisation of Routine Laboratory Values after Gluten Withdrawal in Paediatric Coeliac Patients - Ignacio Ventura; Belén Rodriguez; Sandra Suescum; Fernando Revert; Francisco Revert-Ros; María Antonia Moreno; Jesús A. Prieto-Ruiz; Marcelino Pérez-Bermejo (MDPI AG, 2023)
The assessment of the nutritional and inflammatory status of paediatric patients with coeliac disease is an interesting approach to early diagnosis and functional follow-up. Most authors agree that the normalisation of symptoms takes about one year. The aim of the study was to evaluate the clinical manifestation and normalisation of routine analytics in Spanish children diagnosed with celiac disease. Methods: We performed a retrospective case-control study in Spanish paediatric patients, including 21 celiac patients and 20 healthy controls. The 21 patients selected in the case-control study were followed for 5 years after starting a gluten-free diet (GFD). All patients had type 3 villous atrophy according to the Marsh-Oberhuber classification. A total of 39 blood samples were taken before the start of the GFD, and 109 were taken after. Twenty control sera from healthy donors were used for comparison. Results: We found that patients had a subclinical but statistically significant increase in blood calcium, transaminases, and white blood cells, and a decrease in serum iron, at the time of diagnosis. Our study also shows that analytical values normalise within five years on a gluten-free diet. Conclusions: The use of a combination of subclinical changes, including low iron, high calcium, elevated leukocytes, lymphocytes, and ALT levels in blood samples, together with a low growth percentile, is pertinent in detecting coeliac disease. This set of parameters could help in the diagnosis of patients without clinical symptoms. We can also show that the levels of Fe, Ca, transaminases, and leucocytes remain subclinically altered after 3 years, despite the gluten-free diet.